Mentoring for the Competition: Implementation of Seven Dimensions of Resilient Elderly in Elderly Activity Groups in Lamper Krajan Area - Pustika Dewi, Restu Ayu Eka; Arumsari, Wahyuni; Siti Marchamah, Dwi Nur (Society : Jurnal Pengabdian Masyarakat, 2025)
Aging is a natural process experienced by all living beings, including humans. As people age, they often experience a decline in cognitive and physiological functions. This decline increases the risk of degenerative diseases such as hypertension, diabetes, and cancer, which can significantly impact the quality of life and productivity of the elderly. The concept of the Seven Dimensions of Resilient Elderly serves as a framework to enhance the quality of life and promote more productive living for the elderly. By implementing the Seven Dimensions of Resilient Elderly, the quality of life for older adults can be significantly enhanced, enabling them to lead more productive lives. The objective of this community service initiative is to mentor the volunteers of the Elderly Family Development Group, known as "Bina Keluarga Lansia Mawar (BKL Mawar)” in Lamper Krajan as they prepare to participate in the city-wide competition in Semarang. However, the program faced challenges, including the volunteers' limited understanding of the Seven Dimensions of Resilient Elderly and low levels of community participation in activities organized by BKL Mawar RW 02. The mentoring activities were conducted between April and May 2024, beginning with an analysis of existing issues and discussions to identify priority activities. Subsequent mentoring sessions focused on the practical implementation of the Seven Dimensions of Resilient Elderly within BKL Mawar's programs. The program's outcomes demonstrated significant improvements in the volunteers' understanding of the Seven Dimensions of Resilient Elderly and their application in activities. This enhanced understanding contributed to improving the quality of life for the elderly in RW 02 Lamper Krajan, Lamper Lor, South Semarang, and increased the group's overall preparedness for the competition.